2019
DOI: 10.3390/su11174596
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Multilevel Perception of Safety Climate on Taiwanese Construction Sites

Abstract: This study investigates multilevel differences in safety climate (SC) perception dimensions between management and laborers on Taiwanese construction sites. With Taiwan’s high rate of construction site safety incidents, implementing successful safety strategies requires understanding differences in SC perceptions between management and laborers. This study used a structured SC questionnaire with responses from 74 managers and 261 laborers. The analysis of collected data includes (1) descriptive statistics comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Secondly, to further enhance safety climate, it is vital for an organization to have a positive safety culture, which also influences safety performance. Management should build communication channels and support workers with a positive organizational culture as well as ensure that their workers are protected, regardless of their background or employment type [ 17 ]. High-level supervisors have a significant role in facilitating the link between organizational safety climate and safety performance [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, to further enhance safety climate, it is vital for an organization to have a positive safety culture, which also influences safety performance. Management should build communication channels and support workers with a positive organizational culture as well as ensure that their workers are protected, regardless of their background or employment type [ 17 ]. High-level supervisors have a significant role in facilitating the link between organizational safety climate and safety performance [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Employees of companies with high levels of safety climate behave safely, and they perceive that they are encouraged to retain good safety practices in spite of high production pressure [ 20 ]. A study in Taiwan concluded that the safety climate perception of management is higher than that of laborers and that this difference can be used to improve strategies for enhancing safety climate on construction sites [ 17 ]. Improving the overall construction safety levels is the responsibility of construction managers, as they enhance safety perception by safety training and better practices [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The age characteristic was expressed in non-overlapping year ranges, nationality was expressed in citizenship groups, education was expressed in the highest level of qualification attained, the occupation was expressed in the general job domains of participants, years of experience was expressed in ranges of non-overlapping years spent in the construction profession, and trade specialty was expressed in specific construction activities. These sociodemographic characteristics were used based on several relevant studies [ 5 , 20 , 24 , 28 , 32 , 33 , 34 ] and were found to be the most applicable to the Saudi Arabian construction environment. Other sociodemographic characteristics which have been used in many studies, such as alcohol consumption, were not considered due to being inapplicable to the Saudi Arabian construction industry, as drinking is considered prohibited in the country.…”
Section: Methodsmentioning
confidence: 99%
“…Disparities in trade safety climate perceptions exist and may be associated with changes in tasks, environment, and exposure to risk [ 32 ]. For instance, the safety climate perception of management-level staff is higher than that of labor-level staff [ 33 ]. Similarly, different trades within the construction industry may not share the same risks and hazards.…”
Section: Introductionmentioning
confidence: 99%
“…The 18 selected SFs were assessed using principal component analysis (PCA) with a follow up varimax rotation. PCA generates sets of linear combinations of variables to illuminate the variance observed in the data collected in the surveys [52]. This type of analysis reduces the data being observed to a set of linear related factors.…”
Section: Extracting Sfs Of Ssmmentioning
confidence: 99%